Degradation of Oxytetracycline and Chlortetracycline by Fenton Process - Çelik, Murat; Çelik, Aytekin; Aydın, Ekrem; Gürtekin, Engin (My University, 2023)
In this study, degradation of oxytetracycline (OTC) and chlortetracycline (CTC) was investigated by Fenton process. In experimental studies conducted for this purpose, different values of pH, Fe2+ concentration, H2O2 concentration and reaction time were tested as important parameters for the Fenton process and optimum conditions for OTC and CTC removal were determined. For both antibiotics, the optimum values of the parameters in the Fenton process were the same, and these values were found to be 3 for pH, 20 mg/L for Fe2+ concentration, 25 mg/L for H2O2 concentration, 5 min for reaction time. Under these optimum conditions, OTC degradation was 100%, CTC degradation was 99.68%, chemical oxygen demand (COD) removal efficiency for oxytetracycline (O-COD) was 89.6%, COD removal efficiency for chlortetracycline (C-COD) was 88.5%. These results show that the Fenton process is an effective method that can be used for OTC and CTC degradation.
Keywords: Oxytetracycline; Degradation; Fenton process; Chlortetracycline